2019
DOI: 10.21037/atm.2019.09.38
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of human cervical cancer cell invasion by IL-37 involving runt related transcription factor 2 suppression

Abstract: Background: IL-37 is a newly anti-inflammatory cytokine whose function is largely unknown in cancer.Our preliminary experiment found IL-37 could inhibit the invasion of human cervical cancer (CC) cells and influence the expression of RUNX family whose function was also unclear in CC. The present study aims to further investigate the effects of IL-37 on cell invasion and runt related transcription factor 2 (RUNX2) expression in CC cell lines.Methods: Firstly, plasmid overexpressing IL-37 or RUNX2 was transfecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…While in cervical cancer, knockdown of CCAT1 prevented the tumor progression by blocking the cell growth, migration, invasion and EMT by downregulating RUNX2 [24]. Additionally, upregulation of RUNX2 at least partly recovered the cell invasion reduced by IL-37 in cervical cancer cells [25]. Likewise, our in vivo experiments revealed that RUNX2 restoration counteracted the inhibitory effect of miR-130a-5p on tumor formation.…”
Section: Discussionmentioning
confidence: 52%
“…While in cervical cancer, knockdown of CCAT1 prevented the tumor progression by blocking the cell growth, migration, invasion and EMT by downregulating RUNX2 [24]. Additionally, upregulation of RUNX2 at least partly recovered the cell invasion reduced by IL-37 in cervical cancer cells [25]. Likewise, our in vivo experiments revealed that RUNX2 restoration counteracted the inhibitory effect of miR-130a-5p on tumor formation.…”
Section: Discussionmentioning
confidence: 52%
“…Furthermore, runt related transcription factor 2 (RUNX2) is a member of the RUNX family that activates genes associated with tumorigenesis and metastasis, promoting tumor cell invasion in cancer. IL-37 overexpression significantly inhibits RUNX2 mRNA and protein expression (84), thus markedly inhibiting cell invasion.…”
Section: Suppression Of Cancer By Il-37 Il-37-induced Effects On Tumor Angiogenesis Migration and Progressionmentioning
confidence: 97%
“…While in cervical cancer, knockdown of CCAT1 prevented the tumor progression by blocking the cell growth, migration, invasion and EMT by downregulating RUNX2 [24]. Additionally, upregulation of RUNX2 at least partly recovered the cell invasion reduced by IL-37 in cervical cancer cells [25]. Likewise, out in vivo experiments revealed that RUNX2 restoration counteract the inhibitory effect of miR-130a-5p on tumor formation.…”
Section: Discussionmentioning
confidence: 91%